Edge detection in digital images using fuzzy numbers - Boaventura, Inês A.G. [UNESP]; Gonzaga, Adilson (Inderscience Publishers, 2009)
The purpose of this paper is to introduce a new approach for edge detection in grey shaded images. The proposed approach is based on the fuzzy number theory. The idea is to deal with the uncertainties concerning the grey shades making up the image and, thus, calculate the appropriateness of the pixels in relation to a homogeneous region around them. The pixels not belonging to the region are then classified as border pixels. The results have shown that the technique is simple, computationally efficient and with good results when compared with both the traditional border detectors and the fuzzy edge detectors. Copyright © 2009, Inderscience Publishers.
Keywords: Edge detector; Fuzzy numbers; Image processing; Computationally efficient; Digital image; Edge detectors; Homogeneous regions; New approaches; Edge detection; Fuzzy rules; Fuzzy sets; Imaging systems; Number theory; Pixels; Detectors